Process safety in upstream oil and gas (Wiley, 2021)
"Process safety has been in use in downstream portions of the oil, gas, and chemicals industries for decades both in the U.S. and internationally. Its use in upstream, especially in the U.S., has started much more recently prompted by incidents and regulatory changes"-- Provided by publisher.
Keywords: Oil fields -- Safety measures.; Gas wells -- Safety measures.; Petroleum industry and trade -- Safety measures.; Gas industry -- Accidents.; elektronické knihy; electronic books